Pemanfaatan Loose Parts dalam Pengembangan Kreativitas Anak Usia 5-6 Tahun di PAUD Mutiara Hati Desa Pangek - Ipana, Widia Dwi (ICEJ : Islamic Childhood Education Journal, 2024)
Creativity is an important thing in life, especially in early childhood because it can make people more productive. Developing creativity through Loose Parts media, this media is very appropriate for attracting children's attention so that they always want to be creative well and correctly. This research also aims to determine the use of Loose Parts in developing the creativity of children aged 5-6 years at PAUD Mutiara Hati Pangek Village. This research is descriptive qualitative research, namely providing a report on research results by describing and explaining the data obtained regarding the use of loose parts media in developing children's creativity. Then data collection techniques use observation, interview and documentation techniques. Data analysis is carried out in 3 stages, namely carrying out data reduction or selecting data that is considered important and discarding data that is not needed, then presenting the selected data so that conclusions can be drawn. The results of this research show that the use of loose parts is carried out through several stages, namely the planning stage, implementation stage, and evaluation or assessment stage. The results of increasing children's creativity are that children are able to create works according to their abilities, so that they can develop children's creativity.